Hubungan Penggunaan Kontrasepsi MKJP (Metode Kontrasepsi Jangka Panjang) dengan Kejadian Stunting Di Wilayah Kerja Upt Puskesmas Kramatwatu Tahun 2023: The Relationship Between the Use of MKJP Contraceptives and the Incidence of Stunting in the Work Area of ​​the Kramatwatu Health Center UPT in 2023 - Maulida Rahayu, Antika; Nurkhayati, Etty (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Stunting is a chronic growth disorder caused by a lack of nutritional intake or malnutrition for a long time, especially in the first 1000 days of life. This study aims to determine the Relationship between the Use of MKJP Contraceptives and the incidence of Stunting in the Work Area of ​​the Kramatwatu Health Center UPT in 2023. The method used in this study is quantitative using a cross-sectional research design. The results of this study using statistical tests obtained a p value = 0.000. The value (p <0.05) so that the conclusion is that there is a Relationship between the Use of MKJP Contraceptives and the incidence of Stunting in the Work Area of ​​the Kramatwatu Health Center UPT in 2023. It is recommended for the Kramatwatu District Health Center UPT to further promote the benefits of MKJP contraceptives in preventing stunting.